Effects of spironolactone on serum markers of fibrosis in people at high risk of developing heart failure: rationale, design and baseline characteristics of a proof‐of‐concept, randomised, precision‐medicine, prevention trial. The Heart OMics in AGing (HOMAGE) trial. (16th January 2020) - Pellicori, Pierpaolo; Ferreira, João Pedro; Mariottoni, Beatrice; Brunner‐La Rocca, Hans‐Peter; Ahmed, Fozia Z.; Verdonschot, Job; Collier, Tim; Cuthbert, Joe J.; Petutschnigg, Johannes; Mujaj, Blerim; Girerd, Nicolas; González, Arantxa; et al.
Abstract : Aims: Asymptomatic patients with coronary artery disease (CAD), hypertension and/or type 2 diabetes mellitus (T2DM) are at greater risk of developing heart failure (HF). Fibrosis, leading to myocardial and vascular dysfunction, might be an important pathway of progression. The Heart OMics in AGing (HOMAGE) trial aims to investigate the effects of spironolactone on serum markers of collagen metabolism and on cardiovascular structure and function in people at risk of developing HF and potential interactions with a marker of fibrogenic activity, galectin‐3. Methods and results: The HOMAGE trial is a prospective, randomised, open‐label, blinded endpoint (PROBE) study comparing spironolactone (up to 50 mg/day) and standard care over 9 months in people with clinical risk factors for developing HF, including hypertension, CAD and T2DM, and elevated plasma concentrations of N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP, 125 to 1000 ng/L) or B‐type natriuretic peptide (BNP, 35 to 280 ng/L). Exclusion criteria included left ventricular ejection fraction < 45%, atrial fibrillation, severe renal dysfunction, or treatment with loop diuretics. The primary endpoint was the interaction between change in serum concentrations of procollagen type III N‐terminal propeptide (PIIINP) and treatment with spironolactone according to median plasma concentrations of galectin‐3 at baseline. For the 527 participants enrolled, median (interquartile range) age was 73 (69–79) years, 135 (26%) were women, 412 (78%) had hypertension, 377 (72%) CAD, and 212 (40%) T2DM. At baseline, medians (interquartile ranges) were for left ventricular ejection fraction 63 (58–67) %, for left atrial volume index 31 (26‐37) mL/m 2, for plasma NT‐proBNP 214 (137–356) ng/L, for serum PIIINP 3.9 (3.1–5.0) ng/mL, and for galectin‐3 16.1 (13.5–19.7) ng/mL. Conclusions: The HOMAGE trial will provide insights on the effect of spironolactone on pathways that might drive progression to HF. Clinical Trial Registration: ClinicalTrials.gov NCT02556450.